Study of Rinago weaving at kampung Inukiran with new equipment design - Muhamad Azlan Daud; Nor Azman Abu; Rozaimi Zakaria; Wardatul Akmam Din (Pusat e-pembelajaran, UMS, 2021)
Rattan weaving products are one of the livelihoods for some villagers in Sabah. A study of Rinago weaving was conducted in Inukiran village, Kudat, Sabah. The group that practices rattan weaving is known as Monungkus. The product produced is known as Rinago weaving. The study was conducted to identify and understand the entrepreneurs and rattan products in Sabah. This study has successfully proposed two more conventional JIG (tools that can move side to side) aids, Pais and Peraut to accelerate the production of rattan weaving products.